Water for rural development: Background paper on water for rural development prepared for the World Bank - Molden, David J.; Amarasinghe, Upali A.; Hussain, I. (International Water Management Institute, 2001)
This paper on Water for Rural Development is divided into two parts. The first part outlines the most important issues from IWMI's point of view on water for rural development, with a focus on developing countries. This part identifies, discusses and provides recommendations for key areas for interventions in water resources development and management in the context of rural development. The second part of the document provides analyses of present and future water resources in the World Bank's defined regions.